2019
DOI: 10.1016/j.arthro.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Returning to High-Impact Sports After Hip Arthroscopy: Are We Shooting Ourselves in the Hip?

Abstract: There is a clear consensus in the literature that professional athletes exhibit high rates of return to sport following hip arthroscopy. As orthopaedic surgeons, we are well equipped to guide athletes back to the field after intraarticular hip injuries. However, returning to high-impact sports and playing through the pain can have implications on long-term health. Literature suggests that former elite athletes are at greater risk for reinjury and developing hip osteoarthritis compared with non-athletes. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Nevertheless, in addition to favorable hip function, athlete passion for sport and social benefits to returning quicker motivate the athlete to RTS. 48 However, the literature does not elucidate the function at which athletes return. Approximately 74.2% to 100% of athletes who returned did so the same or greater level compared with preinjury level, whereas 0% to 25.8% returned to a lower level.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in addition to favorable hip function, athlete passion for sport and social benefits to returning quicker motivate the athlete to RTS. 48 However, the literature does not elucidate the function at which athletes return. Approximately 74.2% to 100% of athletes who returned did so the same or greater level compared with preinjury level, whereas 0% to 25.8% returned to a lower level.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that in addition to favorable hip function, an adolescent's passion for the sport and the vast social benefits of returning to sport motivate an adolescent athlete to return to play. 4,47 Team sports provide an incredible platform for adolescents to achieve goals, build selfesteem, and bond with their peers. A systematic review on the psychosocial benefits of sports participation found that adolescents who engaged in sports exhibited increased confidence, emotional regulation, self-knowledge, and cooperation with peers.…”
Section: Discussionmentioning
confidence: 99%
“…10 This is likely explained by the fact that professional athletes have (1) more time to dedicate to the rehabilitation process, (2) direct and indirect financial interests, and (3) social pressure from the team. [11][12][13] In addition, it has been reported that rates of RTS after hip arthroscopy changes over time, with lower rates in the first year after surgery, probably due to the long rehabilitation process, and at follow-up longer than 3 years, likely because of persistent hip pain. 7 It was with great interest I read the article entitled "Return to Play in Amateur Soccer Players Undergoing Hip Arthroscopy: Short-to Mid-Term Follow-Up" 14 by Ortiz-Declet, Yuen, Schwarzman, Chen, Perets, and Domb.…”
Section: See Related Article On Page 442mentioning
confidence: 99%